Hyperflexibility. A feature of e-commerce organisations = Hiperelastyczność. Cecha organizacji na rynku e-commerce - Bieńkowska, Joanna; Sikorski, Czesław (Zielona Góra: Faculty of Economics and Management Press)
The paper is sacrificed analysis of conditions organizational activity on e-commerce business and desired ways of management. Organizations on e-commerce business must be hyper-flexible because of stormy environment and high level of competition. Hyperflexibility means ability to creating new organizational forms so as to realization of different projects collaboration with other organizations and utilizing strange resources. The main condition of Hyperflexibility is pragmatic organizational culture and such its attributes as confidence, tolerance and fluent identity.
Keywords: e-commerse; hiperelastyczność; kultura organizacyjna; pragmatyzm; flexibility; organizational culture; pragmatism